An Epidemiological Study on Disability Parameters in Injury Mechanisms in Jamnagar City, Gujarat - Deepak B Sharma; B S Yadav (Medsci Publications, 2016)
Background: Today accidental injuries constitute the major threat to our young people and those in the prime of their lives and productivity. Many of the injured are left with either temporary disability or permanent disability. Methods: A cross sectional study was conducted on injuries from November-2004 to September 2005 in areas of Jamnagar city and total study subjects were 1496. Total 300 families were studied and 1496 participants. Aims: To study various disability parameters in different injury mechanisms in Jamnagar city, Gujarat Results: Out of total 177, only 3 (1.69%) had permanent disability.153 (86.44%) persons had disability for 1-5 days. 1 (1.63%) was disabled due to road traffic accidents, 1 (2.12%) was disabled due to falls .6 (3.38%) persons were dependent on others for help. Household income declined in 72 (40.44%) cases of injured subjects as a result of injury. Of 178, 9 (5.05%) sold things for treatment, 56 (34.46%) borrowed money. 9 (5.05%) had fear, 8 (4.49%) suffered from PTSD, 5 (2.80%) had family quarrels and 1 (0.56%) suffered from depression. Conclusions: The study revealed many socio-economic issues and psychological effects after injuries. The after results from injuries are quite appealing and leads to many compromises in own life and other family members life.